2015
DOI: 10.1152/jn.00374.2015
|View full text |Cite
|
Sign up to set email alerts
|

Spinal 5-HT7 receptors induce phrenic motor facilitation via EPAC-mTORC1 signaling

Abstract: Fields DP, Springborn SR, Mitchell GS. Spinal 5-HT 7 receptors induce phrenic motor facilitation via EPAC-mTORC1 signaling. J Neurophysiol 114: -2022. First published August 12, 2015 doi:10.1152/jn.00374.2015.-Spinal serotonin type 7 (5-HT 7 ) receptors elicit complex effects on motor activity. Whereas 5-HT 7 receptor activation gives rise to long-lasting phrenic motor facilitation (pMF), it also constrains 5-HT 2 receptor-induced pMF via "cross-talk inhibition." We hypothesized that divergent cAMP-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Intrathecal EPACa (10μL, 100μM) elicited pMF (Fig. 2, B; 58.9 ± 8.2% 90 min post-injection; n = 6; p < 0.001) similar to our previous report (Fields et al, 2015). EPACa induced pMF was attenuated by EPACi (Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Intrathecal EPACa (10μL, 100μM) elicited pMF (Fig. 2, B; 58.9 ± 8.2% 90 min post-injection; n = 6; p < 0.001) similar to our previous report (Fields et al, 2015). EPACa induced pMF was attenuated by EPACi (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Aliquots of stock solutions remained viable for up to one week if stored frozen (−20° C) in 100% DMSO; after this time unused drug solutions were discarded. Prior studies using a similar protocol confirmed that EPACa is a selective EPAC activator (Fields et al 2015) and DOI is a selective 5-HT 2A receptor agonist (MacFarlane et al 2011). Separate studies using cell culture assays have shown that ESI-05 and Rp-8-Br-cAMP are selective inhibitors of EPAC (Tsalkova et al 2012; Rehmann 2013) and PKA (Poppe et al 2008; Harmati et al 2011) respectively (Table 1).…”
Section: Materials/methodsmentioning
confidence: 95%
See 3 more Smart Citations